Differentiation of Human and Mouse Embryonic Stem Cells along a Hepatocyte Lineage - Hitoshi Shirahashi; Jian Wu; Naoki Yamamoto; Andreea Catana; Henning Wege; Brook Wager; Kiwamu Okita; Mark A. Zern M.D. (Cell Transplantation, 2004)
Embryonic stem (ES) cells may differentiate along a hepatocyte lineage; however, currently there are no reports of culture conditions yielding high levels of hepatocyte-specific gene expression in these cells. We investigated culture conditions for differentiating ES cells into hepatocyte-like cells in vitro. Various combinations of culture media, growth and differentiation factors, and substratum precoatings were evaluated, and it was determined that a combination of Iscove's modified Dulbecco's medium with 20% fetal bovine serum, human insulin, dexamethasone, and collagen type I precoating was optimal for directing mouse ES cells along a hepatocyte lineage. Treatment of mouse ES cell with the optimal condition led to prealbumin gene expression 20% as high, and albumin synthesis 7% as high, as in mouse liver. The optimal culture condition also induced albumin gene expression in differentiated human ES cells 1% as high as in normal human hepatocytes as shown by Western blot analysis, and cells were positive for human albumin by immunocyto-chemistry. In addition, our optimal condition led to high levels of albumin gene expression in primary mouse hepatocytes after 35 days of culture, levels 10-fold higher than with other hepatocyte differentiation media. In conclusion, our optimal condition directed both mouse and human ES cells along a hepatocyte lineage. This represents the initial step in establishing cell lines that can be employed in cell-based therapeutics in humans and for toxicology and pharmacology studies.